The influence of immuno-contraception on the ecology of African savanna elephants (Loxodonta africana) in a small game reserve in the Eastern Cape, South Africa - Fowler, Natalie Rebecca (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
African savanna elephants (Loxodonta africana) can alter the vegetation structure on a landscape which has both positive and negative consequences for biodiversity. This ecological role can be dependent on the density of elephants in a given area and how the area is transformed. Elephants are currently listed as an endangered species on the International Union for Conservation of Nature (IUCN) global red list. Despite this endangered status, strong conservation efforts in southern Africa have increased elephant numbers in protected areas. In South Africa, many of these protected areas are small (<1000 km2) and fenced. Thus, without the freedom to roam over large areas, elephant impacts on vegetation and other ecosystem processes may be exacerbated. Increased growth rates and higher population densities, have prompted wildlife managers to explore several population-level management techniques to slow elephant growth rates in small, protected areas. One such technique is the use of immuno-contraception. My study focused on three datasets (Pre, During and Post porcine zona pellucida (PZP) treatments) of one elephant population over an 18-year period in a small game reserve in the Eastern Cape, South Africa. The first aim of my study was to compare the female demography and reproductive parameters of treated (with PZP) and non-treated females (no PZP). I predicted that the population growth would decrease as more elephant cows were contracepted as well as them having longer inter-calving intervals than non-treated cows. Further, I predicted that there would be a skewed sex ratio of male calves born to treated cows. Lastly, I predicted that fertility rates would be lower in treated cows than in non-treated cows. I calculated the annual population growth rates, inter-calving intervals, sex ratios, age at first calving, fecundity rates and fertility rates of all breeding cows. Population growth rates were similar to other managed populations although, compared to a relatively untouched elephant population, annual growth rates in my study site were high. The inter-calving intervals and age at first birth were low compared to other African protected areas which were most likely influenced by the use of PZP, rainfall and a lack of density dependence. Treated cows did not have longer inter-calving intervals compared to non-treated cows nor was there a male biased sex ratio of the offspring of treated cows. The second aim was to assess the spatial ecology of this elephant population and how it may be influenced by immuno-contraception. I predicted that the use of PZP would increase the elephant herd's core range as there were fewer reproducing cows. I also predicted that PZP would alter the elephant's habitat use making them less selective in terms of the vegetation types they selected. I compared the home ranges of the elephant population among the three treatments (Pre PZP, During PZP and Post PZP treatment). Home ranges were larger when elephants were treated with PZP compared to the Pre and Post treatments. The herd utilized most of the reserve during the use of PZP whereas prior to contraception, their space use was mostly concentrated on the eastern side of the reserve. Additionally, the vegetation utilization was inconsistent across the differing timeframes, specifically between pre PZP and during PZP. Prior to the use of PZP, the elephant herd utilized the old lands and riverine thicket the most whereas during the use of PZP, the grasslands and karroid habitats were used the most. The most likely influence of the changes in home ranges and vegetation utilization were rainfall, the use of PZP and resource availability. My results suggest that the use of PZP is essential for controlling elephant population numbers. However, there may be some long-term effects (e.g., behavioural changes) of the use of PZP in elephant populations in small game reserves. Thus, I recommend continued monitoring of all aspects of elephant ecology on reserves where PZP is used as a contraceptive technique.
Keywords: African elephant -- South Africa -- Eastern Cape; African elephant Ecology -- South Africa -- Eastern Cape; Contraception, Immunological; African elephant Habits and behavior; Porcine zona pellucida; African elephant Reproduction